Digital Audio Applications on Students’ Abilities in EFL: A Systematic Literature Review - Silvia, Sifa; Santosa, Made Hery (EDUCAFL: Journal on Education of English as Foreign Language, 2023)
This systematic review aims to analyze and summarize previous studies on the use of digital audio applications like Spotify or JOOX to improve the abilities of Indonesian EFL learners who face difficulties in learning English due to differences in structure, pronunciation, and vocabulary. This study utilized the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol to obtain the results. A comprehensive search was conducted on Google Scholar and Open Knowledge Maps, reviewing a total of ten journal articles published between 2019 and 2023. The selection process followed a systematic approach, adhering to specific inclusion and exclusion criteria. The result found the use of digital audio applications shows a positive impact on students’ abilities. The findings assert that digital audio applications improve students’ abilities with features, English songs, and podcasts. The previous studies agree that digital audio application gives students easier ways to learn pronunciation and vocabulary with features, like lyrics, curated playlists, and English songs. The practical implication of this study is that teachers are advised to use digital audio applications to support students’ abilities with clear objective and careful considerations in using digital audio applications as teaching media.